Depth Image Assisted Aiming for Scoring Goal in Wheeled Soccer Robot - Kusuma, Hendra; Samhan, Dzulfikar Ahmad; Tasripan, Tasripan; Dikairono, Rudy (JAREE (Journal on Advanced Research in Electrical Engineering), 2024)
Wheeled soccer robot, as an automatic robot, required to have an advanced decision making system based on information it grasp from its surrounding. One of the most crucial decision making ability is to determine aiming angle when it is scoring goal.This research will enhance the aiming ability for scoring goal by predicting unguarded area of goal. Combination of depth image and RGB image information will be used to predict the position of unguarded space in goal. This position will be converted into aiming angle for the robot. Intel Realsense D435i depth camera will be used to get RGB and depth image simultaneouslyBy using this method, the system is capable to predict unguarded area in all of 60 test points, with 1.3% average error for the predicted coordinate.